Fundamentals of bioorganic chemistry: textbook for foreign students of Medical Higher Educational Institutions - Zurabyan, S. E. Sergey Eduardovich (21 век, 2004)
The textbook is based on modern organic chemistry and considers the structure and chemical transformations of organic compounds, especially those that have biological importance. Special attention is given to the chemical reactions that have analogies in living systems. The book contains about 250 problems on all topics and solution for them. This book conforms to the Federal educational program on Bioorganic Chemistry for medical schools and universities/ It is meant for students who study Bioorganic Chemistry during one them. The book may also be useful for teachers and students of specialized secondary schools with instruction conducted in English and colleges, whose main interest in medicine, pharmacy, biology, and agriculture.